2024
DOI: 10.1161/circresaha.123.322910
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-Mediated Activation of v-ATPase by Nicotinamide Mononucleotide Ameliorates Lipid-Induced Cardiomyopathy by Repressing the CD36-TLR4 Axis

Shujin Wang,
Yinying Han,
Ruimin Liu
et al.

Abstract: BACKGROUND: Chronic overconsumption of lipids followed by their excessive accumulation in the heart leads to cardiomyopathy. The cause of lipid-induced cardiomyopathy involves a pivotal role for the proton-pump vacuolar-type H + -ATPase (v-ATPase), which acidifies endosomes, and for lipid-transporter CD36, which is stored in acidified endosomes. During lipid overexposure, an increased influx of lipids into cardiomyocytes is sensed by v-ATPase, which then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Alternatively, NMN has been shown to enter muscle cells after a dephosphorylation step by the CD73/NT5E (cluster of differentiation/ ecto-5'-nucleotidase) at the membrane, which converts NMN into nicotinamide riboside that in turn enters cells through the nucleoside equilibrative transporters and is converted to NMN by the NMRK2 (nicotinamide riboside kinase 2). 10,11 The study by Wang et al 4 shows that NMN supplementation restores NAD + levels and the association of the glycolytic enzyme aldolase with the v-ATPase V1 subcomplex, accompanied by a reassembly with V0 subcomplex. The test of this hypothesis was actually driven by previous research from other teams working in yeast who had shown that glycolytic complexes assembly with v-ATPase subunits can lead to v-ATPase reassembly on glucose restoration in the medium after a period of starvation, allowing the localized production of ATP for the use of the v-ATPase proton pump and resulting in the reacidification of endosomes.…”
Section: Article See P 505mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, NMN has been shown to enter muscle cells after a dephosphorylation step by the CD73/NT5E (cluster of differentiation/ ecto-5'-nucleotidase) at the membrane, which converts NMN into nicotinamide riboside that in turn enters cells through the nucleoside equilibrative transporters and is converted to NMN by the NMRK2 (nicotinamide riboside kinase 2). 10,11 The study by Wang et al 4 shows that NMN supplementation restores NAD + levels and the association of the glycolytic enzyme aldolase with the v-ATPase V1 subcomplex, accompanied by a reassembly with V0 subcomplex. The test of this hypothesis was actually driven by previous research from other teams working in yeast who had shown that glycolytic complexes assembly with v-ATPase subunits can lead to v-ATPase reassembly on glucose restoration in the medium after a period of starvation, allowing the localized production of ATP for the use of the v-ATPase proton pump and resulting in the reacidification of endosomes.…”
Section: Article See P 505mentioning
confidence: 99%
“…In the current issue of Circulation Research, Wang et al 4 specifically address the question of reducing the impact of cardiac lipotoxicity by assessing the benefit of specific nutrients supplementation to inhibit the fatty acid-induced increase in recycling of the fatty acid transporter CD36 (cluster of differentiation 36) at the membrane. Indeed this mechanism traps the cardiomyocytes in a vicious circle of further enhancement of lipid uptake reinforcing lipotoxicity.…”
Section: Article See P 505mentioning
confidence: 99%